A simple and feasible fluorescent approach for rapid detection of hexavalent chromium based on gold nanoclusters. (15th February 2023) - Liu, Feiyan; Lai, Xuandi; Zhao, Shengliang; Lu, Zhiyang; Han, Peigang; Chen, Liqiong
Highlights: The AuNCs based on d -histidine and polylysine was first designed to detect Cr 6+ . The detection mechanism was aggregation of AuNCs and FRET between AuNCs and Cr 6+ . The proposed fluorescence method possessed high sensitivity and selectivity. The proposed method possessed feasibility of usage in actual system. Abstract: Hexavalent chromium (Cr 6+ ) owns hypertoxicity, non-biodegradability, and carcinogenicity, thus the detection of Cr 6+ is of paramount significance for environmental monitoring and human health maintenance. Herein, a simple, rapid, and feasible fluorescent method based on gold nanoclusters (AuNCs) was established for determination of Cr 6+ . The AuNCs was coated by a simple and fast one-pot method using d -histidine (d -His) and polylysine (P-Lys) as stabilizers and reductants, which could be quenched by the addition of Cr 6+ owing to the aggregation of AuNCs and fluorescence resonance energy transfer (FRET) between AuNCs and Cr 6+ . Under the optimal conditions, the fluorescent sensor exhibited good linearity within 10–10000 μg/L with limit of detection of 7.2 μg/L. The developed sensor possessed favorable sensitivity and selectivity. Additionally, the proposed method also had favorable recovery with good precision and accuracy within the actual sample, including celery cabbage, rice, capsule shell, and river water.